“We Need to Put Things Back to Normal.” Interview with Ole Bjerg - Bjerg, Ole (Экономическая социология, 2018)
An interview with Ole Bjerg, an Associate professor at Department of Management, Politics and Philosophy (Copenhagen Business School), was conducted in May 2018 during his visit in Moscow. Prof. Bjerg has visited HSE and presented a Russian translation of his book Making Money: The Philosophy of Crisis Capitalism [Bjerg 2014]. An interview was taken by Elena Gudova, a junior researcher at the Laboratory for Studies in Economic Sociology, Higher School of Economics. During his presentation Ole Bjerg focused on the issue of introducing e-krona into Swedish monetary system and making money “full-fat” again. The initiative should give power in money emission back to Central Bank and put it under more transparency and control—we’ve been living in a world where commercial banks simply create money for too long. Bjerg suggests that interest toward money and finance is growing both in academia and among ordinary citizens in many countries. After the economic crisis of 2008–2009 it has become obvious that much of what is going on in the society is deeply connected to money, and the level of critical reflection has substantially increased.